Hubungan Pengetahuan, Sikap dan Persepsi Ibu dengan Status Imunisasi Dasar Di Wonokusumo - Tri Anisca Dillyana (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2019)
Background: Basic immunization is the first immunization that should be given to everyone, especially infants and children from birth to protect lifes from dangerous diseases. The immunization program in Indonesia requires every infant (0-11 months) to receive complete basic immunization consist of 1 dose of Hepatitis B, 1 dose of BCG, 3 doses of DPT-HB-Hib, 4 doses of polio, and 1 dose of measles. Basic Immunization in RW 8 Wonokusumo Urban Village in 2017 has not reached the target. Only 73 infants (67%) of 108 have received complete basic immunization which the target of Puskesmas is 95%. This study aims to know the correlation of knowledge, attitude and mother perception with the basic immunization status in Wonokusumo. This study is an observational analytic research with quantitative approach. The study was cross sectional with a sample of 39 respondents. The sampling technique used is purposive sampling. Respondents in this study are mothers who have children under three and have KMS in RW 8 Wonokusumo Urban Village. Primary data collection techniques obtained from questionnaires while secondary data obtained from Wonokusumo Puskesmas and Surabaya City Health Office reports .The result of bivariate statistic test shows that there is correlation between knowledge, attitude, and mother perception with the immunization status of children under three with p = 0,001 (p < 0,05). Conclusion: There is correlation between knowledge, attitude, and mother perception with the basic immunization status in RW 8, Wonokusumo Village.